2019
DOI: 10.1016/j.chb.2018.02.027
|View full text |Cite
|
Sign up to set email alerts
|

The role of learning analytics in networking for business and leisure: A study of culture and gender differences in social platform users

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…After analyzing the 15 studies using Discourse Textual Analysis (DTA) [Moraes and Galiazzi, 2007], nine topics emerged from the studies and some have sub-topics (table 3). [Benson and Filippaios, 2019] Regarding the algorithm bias topic, Knox (2017) considered that culture is not only embedded in learning analytics systems but is also reshaped through the power of its algorithms. In this sense, the author developed a project that considered student participation and choice in the learning analytics process as an attempt to foster critical awareness of data capture and analysis.…”
Section: Use Of Critical Lens In Lamentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing the 15 studies using Discourse Textual Analysis (DTA) [Moraes and Galiazzi, 2007], nine topics emerged from the studies and some have sub-topics (table 3). [Benson and Filippaios, 2019] Regarding the algorithm bias topic, Knox (2017) considered that culture is not only embedded in learning analytics systems but is also reshaped through the power of its algorithms. In this sense, the author developed a project that considered student participation and choice in the learning analytics process as an attempt to foster critical awareness of data capture and analysis.…”
Section: Use Of Critical Lens In Lamentioning
confidence: 99%
“…Authors found that region, neighborhood poverty level, and prior education are strong predictors of overall learning outcomes. Benson and Filippaios (2019) used culture (nationality) and gender as variables to predict user engagement in social networking sited.…”
Section: Use Of Critical Lens In Lamentioning
confidence: 99%
“…While in the process of improving themselves to face the global market, the SME is faced with the Covid-19 pandemic situation which of course makes it more difficult to move causing a significant decline in growth and development [5]. One solution in the context of recovering conditions and business sustainability is to strengthen collaboration between SMEs [5] where collaboration allows SMEs to carry out positive activities such as exchanging information and business cooperation in order to strengthen each other [6], [7]. However, the current implementation of SME collaboration still tends to be weak due to the lack of motivation to collaborate and lack of awareness of collaboration [5].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, SMEs cannot be separated from the influence of local wisdom as one of the roots of thought and behavior. Local wisdom that applies in the community is proven to affect the mindset of each individual [6], [1], [7]. Among the prevailing local wisdom, there is "Silaturrahmi" which has the principle of establishing closeness with other people [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…The flourishing of SNSs comes essentially from users' frequent information disclosure and opinion sharing (Chen and Sharma, 2013; Cheung et al , 2015; Kwak et al , 2014). These SNSs have offered more chances for many businesses to generate substantial commercial benefits through active user participation (Benson and Filippaios, 2019; Kaplan and Haenlein, 2010; Krasnova et al , 2010). Several potential business benefits may be derived from users who actively provide their personal information on SNSs (Laroche et al , 2012; Liu and Bakici, 2019; Muniz and O'Guinn, 2001).…”
Section: Introductionmentioning
confidence: 99%